Pengaruh Sosialisasi Perpajakan Dan Kualitas Pelayanan Perpajakan Terhadap Kepatuhan Wajib Pajak Dengan Pengetahuan Perpajakan Sebagai Variabel Intervening (Studi Kasus pada Wajib Pajak Orang Pribadi di KPP Pratama Kota Jayapura) - Julian Toyang Kbarek; Linda Y. Hutadjulu; Yohanes C. Seralurin (Fakultas Ekonomi dan Bisnis, Universitas Cenderawasih, 2021)
This study aims to analyze the effect of tax socialization and tax service quality on taxpayer compliance with tax knowledge as an intervening variable. Case study on individual taxpayers at KPP Pratama Papua, Jayapura City.This research was conducted at the KPP Pratama Papua office, in Jayapura City. Collecting data in this study using a questionnaire distributed to individual taxpayers registered at the KPP Pratama Jayapura City. The sampling technique used in this research is purposive sampling. The number of research samples taken were 99 respondents. The data analysis technique uses Partial Least Square (PLS) using Smart PLS 3.0 software.Based on the results of research using Smart PLS as a test tool, it shows that the tax socialization variable has a direct significant effect on tax knowledge. The variable of tax service quality has no direct significant effect on tax knowledge. The taxation socialization variable has no direct significant effect on taxpayer compliance. The variable of tax service quality has no direct significant effect on taxpayer compliance. Tax knowledge variable has a significant effect on taxpayer compliance. The variable knowledge of taxation can have an indirect effect on the socialization of taxation on taxpayer compliance. The variable of tax knowledge can have an indirect effect on the quality of tax services on taxpayer compliance.